Pendampingan Orangtua Dalam Pembelajaran Daring Di Sekolah Dasar: : Evaluasi Pembelajaran Daring Selama Masa Pandemi Covid-19 - Betty Kusumaningrum; Krida Singgih Kuncoro; Tri Astuti Arigiyati; Trisniawati (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
One of the impacts of the Covid-19 pandemic on the education sector is changing the face-to-face learning system into online learning. This research was conducted to find out how the pattern of parental assistance in online learning at the Elementary School (SD) level. The research data were obtained using a questionnaire given online via Google Form to 100 parents of elementary school students who were selected by random sampling method. Based on the research results, it is concluded that parents play a role in assisting the learning process of children at home. Most parents cannot fully assist their children in learning because both parents have to work. As a solution, other family members can accompany their children to learn. Not a few parents also entrust tutors to accompany their children to study because parents do not understand the material provided. Parents have high hopes that teachers in explaining the material are not too fast so that students can understand the material better, communication between students and teachers is more intense, material is integrated with student life, and students acquire skills and character education.